2014
DOI: 10.1111/febs.12786
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial action of transcription factors orchestrates cell cycle‐dependent expression of the ribosomal protein genes and ribosome biogenesis

Abstract: Nucleolar assembly begins at the early G1 phase of the cell cycle and is a hub of ribosomal DNA transcription and rRNA biosynthesis. The newlyformed rRNAs together with ribosomal proteins (RPs) constitute the building block of the ribosomal machinery. Although RPs play a major role in protein biosynthesis, their own regulation and expression is rather poorly understood. In the present study, we investigated the regulation of RP genes RPS27a, RPS24, RPS6, RPL9 and RPL4 in synchronized mammalian cell culture. Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…RPS27A is synthesized as a C-terminal extension of ubiquitin, while ubiquitin is involved in DNA repair, cell-cycle regulation, and protein degradation via the proteasome. The expression of RPS27A is specifically induced in the middle and late G1 phase of the cell cycle, mainly to ensure that the biological process of the cell cycle proceeds smoothly (45). We recognized RPS27A showed decreased expression level comparing with normal samples, indicating that reduced RPS27A expression might be involved in the development of MCI through conducting to arrest of cell cycle.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…RPS27A is synthesized as a C-terminal extension of ubiquitin, while ubiquitin is involved in DNA repair, cell-cycle regulation, and protein degradation via the proteasome. The expression of RPS27A is specifically induced in the middle and late G1 phase of the cell cycle, mainly to ensure that the biological process of the cell cycle proceeds smoothly (45). We recognized RPS27A showed decreased expression level comparing with normal samples, indicating that reduced RPS27A expression might be involved in the development of MCI through conducting to arrest of cell cycle.…”
Section: Discussionmentioning
confidence: 85%
“…that cell cycle-related proteins exhibit abnormal expression in hippocampal neurons of patients with MCI (44,45). RPS27A is synthesized as a C-terminal extension of ubiquitin, while ubiquitin is involved in DNA repair, cell-cycle regulation, and protein degradation via the proteasome.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, not only phosphorylation but also expression of both RPS6 and 4E‐BP1 was reduced upon mTOR inhibition. It has been shown that the synthesis of ribosomal proteins, such as RPS6, is tightly linked to cell cycle progression and remains low during the G 0 phase (Nosrati et al , ), as observed in resting T cells. Thus, it is probable that the antiproliferative effect induced by mTOR inhibitors impairs the expression of RPS6.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of TFs have been implicated in ribosome biogenesis; for instance, roughly 80 factors have been associated in the maturation of the 60S subunit [38]. REPA predicted the following 38 TFs to be associated with the KEGG ribosome pathway (supporting literature is referred to after the corresponding TF): ATF1, ATF2, ATF3, BCL3, BCLAF1, CBX3, CEBPB, CJUN, CREB1 [39], ELF1 [40], ETS1, GABP [41], GR [42], HEY1, IRF3, MTA3, MYBL2, NFATC1, NFIC, NRSF, PML [43], POL2 [37], POU2F2, RFX5, RUNX3, SIN3AK20, SIX5, SP1 [41], SP4, STAT5A, TAF1 [44], TAF7, TBLR1, TCF12, WHIP, YY1 [41], ZNF143, and ZNF263. Thus, we found literature support for 9 (or 24%) of these TFs.…”
Section: Number Of Repa's Predictions Per Gene Setmentioning
confidence: 99%